Study on the genetic diversity of wax trees (Rhus succedanea L.) in Northern mountainous region of Vietnam by SSR and SCoT markers - Hong Chien, Nguyen; Thi Kim Linh, Nguyen; Thi Kim My, Trin; Xuan Truong, Nguyen; Van Chung, Nguyen; Thi Trang, Le; Huu La, Nguyen (Vietnam Journal of Biotechnology, 2021)
<pre style="text-align: justify; text-indent: 17.0pt; tab-stops: 17.0pt 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt; layout-grid-mode: char; margin: 6.0pt 19.85pt .0001pt 17.0pt;">Wax tree has been cultivated to get lacquer, a valuable source of material that is necessary for many industries and handicrafts. Evaluating not only phenotype but also genotype is essential in order to increase the efficiency of new breeding program. In this study, the genetic relationship at the molecular level of 90 wax trees collected in three regions, i.e., Tam Nong, Thanh Son (Phu Tho) and Chiem Hoa (Tuyen Quang), was analyzed by SSR and ScoT markers. The results revealed a significant diversity among the individuals, with similarity coefficient from 0.41 to 0.98. The sample group collected in Chiem Hoa was significantly different from that in Tam Nong. Most of samples which had a high level of genetic similarity, from 0.95 to 0.98, were pairs of samples at the same geographical origin. The high similarity degree of these samples is likely due to the practice of selecting seeds from high-yield wax tree to be kept for seeds. These results provide the necessary information for new wax tree breeding program.